Hollow Manganese Silicate Nanotubes with Tunable Secondary Nanostructures as Excellent Fenton‐Type Catalysts for Dye Decomposition at Ambient Temperature. (7th September 2016) - Hao, Shu‐Meng; Qu, Jin; Zhu, Zhong‐Shuai; Zhang, Xiao‐Ying; Wang, Qian‐Qian; Yu, Zhong‐Zhen
Abstract : Fast diffusion rate of ions and sufficiently exposed active sites are important for catalysts. As a superior but rarely studied Fenton‐type catalyst, unsatisfactory ion diffusion rate of manganese silicate is the exact obstacle for improving its catalytic activity. Here, hierarchical manganese silicate hollow nanotubes (MnSNTs) assembled by tunable secondary structures are precisely fabricated by an efficient hydrothermal method and systematically investigated as Fenton‐type catalysts for the first time. The open end and thin mesoporous walls of the hollow nanotubes help shorten the diffusion pathway of ions and enhance the mass transport. Moreover, the numerous standing small nanosheets endow MnSNTs with higher specific surface area and larger pore volume than the large nanosheets and nanoparticles, and thus expose more active sites for adsorption and catalytic decomposition. MnSNTs are highly efficient in adsorption and catalytic decomposition of cationic dyes with an excellent recycling stability. About 98.1% of methylene blue is catalytically decomposed in 45 min at an ambient temperature of 25 °C. When the temperature increases to 60 °C, only 2 min are required, with a 530% higher kinetic constant than reported. Abstract : Hierarchical manganese silicate hollow nanotubes assembled by tunable secondary structures are fabricated and systematically investigated as Fenton‐type catalysts. About 98.1% of methylene blue is decomposed in 45 min at 25 °C. When the temperature increases to 60 °C, only 2 min are required, with a 530% higher kinetic constant than reported.